2002
DOI: 10.1046/j.1365-2036.2002.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal ulcer healing with 1‐week eradication triple therapy followed, or not, by anti‐secretory treatment: a multicentre double‐blind placebo‐controlled trial

Abstract: Background: In the management of Helicobacter pylori induced duodenal ulcer, it is still controversial whether anti‐secretory treatment needs to be continued following a 1‐week course of eradication therapy. Methods: 150 patients with H. pylori active duodenal ulcer (diameter ≥ 5 mm) were included. After a 1‐week eradication treatment combining omeprazole 20 mg b.d., amoxicillin 1000 mg b.d. and clarithromycin 500 mg b.d. (OAC), patients were randomized to omeprazole 20 mg or placebo for 3 additional weeks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…were assigned to two groups to receive either a placebo or a further 3 weeks of omeprazole. In this study the duodenal ulcer healing rate was the same in both groups suggesting that the proton pump inhibitor need not be continued beyond the antibiotic regimen 50 . A further factor that may influence the outcome is the metaboliser status of the patients.…”
Section: The Proton Pump Inhibitor As Part Of the Eradication Regimenmentioning
confidence: 63%
“…were assigned to two groups to receive either a placebo or a further 3 weeks of omeprazole. In this study the duodenal ulcer healing rate was the same in both groups suggesting that the proton pump inhibitor need not be continued beyond the antibiotic regimen 50 . A further factor that may influence the outcome is the metaboliser status of the patients.…”
Section: The Proton Pump Inhibitor As Part Of the Eradication Regimenmentioning
confidence: 63%
“…Studies assessing ulcer healing with a 7‐day combination of PPI plus two antibiotics are summarized in Table 1 11–34 . In total, 24 studies (2342 patients) were included.…”
Section: Description Of Studies and Efficacy On Ulcer Healingmentioning
confidence: 99%
“…Healing rate (weighted mean) was 86% (95% CI, 84–87%) in all patients (both with H. pylori eradication success and failure), and it was 95% (95% CI, 94–96%) when only patients with H. pylori eradication success were considered. The characteristics of studies included in the meta‐analysis comparing the efficacy on ulcer healing of a 7‐day combination of PPI plus two antibiotics vs. this same regimen but prolonging the PPI for several more weeks are summarized in Table 2 12, 23, 25, 26, 32, 33 . Six studies identified with the defined search strategy fulfilled the inclusion criteria and contained data for the planned comparison.…”
Section: Description Of Studies and Efficacy On Ulcer Healingmentioning
confidence: 99%
See 2 more Smart Citations